2017
DOI: 10.1002/bdd.2115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of multiple cytochrome P450 activities in metabolically inactivated human liver microsomes and roles of P450 2C isoforms in reaction phenotyping studies

Abstract: The fraction of substrate metabolized (f ) can be used to estimate drug interactions and can be determined by comparison of the intrinsic clearances (CL ) of victim drugs obtained from inhibited and uninhibited hepatic enzymes Commercially available human liver microsomes were recently developed in which one cytochrome P450 (P450) isoform is selectively inactivated. These inactivated liver microsomes were used to evaluate the roles of P450 2C isoforms in the depletion and oxidation of probe substrates. Determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…By applying the mechanism-based inactivation of P450 2C9 by tienilic acid, the inhibition ratios of S -warfarin oxidation in vitro were previously shown to be 68 and 76% at substrate concentrations of 1.0 and 10 μM, respectively . These in vivo values were consistent with the f m,P450 2C9 values for S -warfarin of 0.75 and 0.81 found in substrate depletion assays (after chiral separation) at 0.50 and 5.0 μM, respectively (in the presence of the same amount of R -warfarin) . However, while studying the roles of marmoset P450 enzymes in diclofenac oxidations, we recently noticed parallel roles of P450 3A and 2C19 enzymes in diclofenac hydroxylations.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…By applying the mechanism-based inactivation of P450 2C9 by tienilic acid, the inhibition ratios of S -warfarin oxidation in vitro were previously shown to be 68 and 76% at substrate concentrations of 1.0 and 10 μM, respectively . These in vivo values were consistent with the f m,P450 2C9 values for S -warfarin of 0.75 and 0.81 found in substrate depletion assays (after chiral separation) at 0.50 and 5.0 μM, respectively (in the presence of the same amount of R -warfarin) . However, while studying the roles of marmoset P450 enzymes in diclofenac oxidations, we recently noticed parallel roles of P450 3A and 2C19 enzymes in diclofenac hydroxylations.…”
Section: Introductionsupporting
confidence: 79%
“…We previously adopted the approach of selective P450 inhibition to evaluate the different roles of human P450 isoforms, especially P450 2C isoforms, in the oxidation of typical P450 probe substrates . By applying the mechanism-based inactivation of P450 2C9 by tienilic acid, the inhibition ratios of S -warfarin oxidation in vitro were previously shown to be 68 and 76% at substrate concentrations of 1.0 and 10 μM, respectively . These in vivo values were consistent with the f m,P450 2C9 values for S -warfarin of 0.75 and 0.81 found in substrate depletion assays (after chiral separation) at 0.50 and 5.0 μM, respectively (in the presence of the same amount of R -warfarin) .…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The inactivated HLM is then frozen for storage and ready to be used. Silensomes™ provide a convenient (‘thaw‐and‐go’) and more consistent source for reaction phenotyping without the need of adding inhibitors for each experiment (Murayama et al, ). Silensomes™ was used for reaction phenotyping of AZD6738 (Jones, Markandu, Gu, & Scarfe, ) to demonstrate that CYP2C8 played a dominant role in the oxidation of AZD6738 to its sulfoxide metabolite, AZ8982.…”
Section: Reaction Phenotyping To Identify Victim Ddi Riskmentioning
confidence: 99%
“…It was found that desethylamiodarone inactivates CYP1A1, CYP1A2, 2B6 and 2D6 but not CYP3A4. Finally, it is noteworthy that while rCYPs may not be useful for DDI prediction and IVIVE, they are a very useful tool for deducing the mechanism of inactivation of specific CYP isoforms (Murayama, et al, 2018;Orr, et al, 2012).…”
Section: In Vitro Experimental Approaches and Assay Designmentioning
confidence: 99%